Long‐term follow‐up of five yr shows superior renal function with everolimus plus early calcineurin inhibitor withdrawal in the PROTECT randomized liver transplantation study. Issue 6 (10th May 2016) - Sterneck, Martina; Kaiser, Gernot M.; Heyne, Nils; Richter, Nicolas; Rauchfuss, Falk; Pascher, Andreas; Schemmer, Peter; Fischer, Lutz; Klein, Christian G.; Nadalin, Silvio; Lehner, Frank; Settmacher, Utz; et al.
Abstract: Background: The 12‐month (M) PROTECT study showed that de novo liver transplant recipients (LTxR) who switched from a calcineurin inhibitor (CNI)‐based immunosuppression to a CNI‐free everolimus (EVR)‐based regimen showed numerically better renal function. Here, we present the five‐yr follow‐up data. Methods: PROTECT was a randomized controlled study in which LTxR received basiliximab and CNI‐based immunosuppression ± corticosteroids. Patients were randomized 1:1 to receive EVR or continue CNI. Patients completing the core study could enter the extension study on their randomized treatment. Results: A total of 81 patients entered the extension study (41, EVR; 40, CNI). At M59 post‐randomization, the adjusted mean eGFR was significantly higher in the EVR group, with a benefit of 12.4 mL/min using Cockcroft–Gault (95% CI: 1.2; 23.6; p = 0.0301). Also, there was a significant benefit for adjusted and unadjusted eGFR using the four‐variable Modification of Diet in Renal Disease (MDRD4) or Nankivell formula. During the extension period, treatment failure rates were similar. SAEs occurred in 26 (63.4%) and 28 (70.0%) of the patients in EVR and CNI groups, respectively. Conclusion: Compared with the CNI‐based treatment, EVR‐based CNI‐free immunosuppression resulted in significantly better renal function and comparable patient and graft outcomes after five‐yr follow‐up.